The usability, acceptance and changes management of SPS on its effectiveness in secondary schools in Peninsular Malaysia - Wan Mahmud, Wan Marfazila; Ab. Jalil, Habibah (Human Resource Management Academic Research Society, 2022)
Nowadays, information management system plays a vital role in organizations. Schools are among the organizations which utilizes information management system in their operation. The purpose of this research is to identify the level of usability SPS’s, acceptance and change management towards school effectiveness. This research was done for four districts which had been chosen according to states and zones in peninsular Malaysia which had been randomly selected which includes Central Zone (Petaling Perdana district, Selangor), North Zone (North East district, Pulau Pinang), East Zone (Kota Bahru district, Kelantan) and South district (Johor Bahru district, Johor). Descriptive research design and correlation through survey were used in this research. Survey questionnaires were distributed to 385 teachers, whom were the samples of this research. Samples are chosen by stratified random sampling technique and random sampling. Five constructs involved in SPS usability includes SPS quality, SPS information quality, SPS quality service, SPS satisfaction and SPS usage. For SPS acceptance, there are four constructs involved in SPS acceptance, which include performance expectation, effort expectation, social influence and condition of facility. For SPS change management, there are five constructs involved which include awareness, eagerness, knowledge, ability and reinforcement. Statistical descriptive analysis shows school effectiveness are at a low level. Overall, the mean value for SPS usability, SPS acceptance and SPS change management are low. The result is, suggestion towards SPS change management should be encouraged to help teachers prepare and understand the implementation of SPS to increase school effectiveness and school management. This is important to ensure teachers can accept effectively any change taking place in any new change of policy. For SPS usability aspect, researchers suggest the system applied at school to be given high priority and consideration by the policy makers to ensure the system’s application in school is effective and beneficial towards the schools. This is to ensure the school’s effectiveness in a more systematic manner in the effort of improving school management system (SPS).